Optimizing Archives Management in Improving Administrative Order in Islamic Boarding Schools - Amanda, Laila Tri; Silahudin, Agus (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2026)
This research aims to analyze archival management in realizing administrative order at the Hayatuddiyar Islamic Boarding School Pekanbaru. Archives have a strategic role as a center of authentic information and evidence that supports decision-making, planning, and evaluation of institutional performance. This study uses a qualitative approach with an evaluative descriptive design. The informants consist of school principals, administrative staff, and teachers who are selected purposively. Data collection techniques are carried out through observation, in-depth interviews, and documentation, while data analysis uses an interactive model that includes reduction, presentation, and drawing conclusions. The validity of the data was tested through triangulation of sources, techniques, and member checks. The results of the study show that archive management has been run based on four management functions, namely planning, organizing, implementing, and supervising. In the planning stage, inventory, classification, and digitization of cloud-based archives have been carried out, but they have not been supported by formal standard operating procedures (SOPs). The organizing stage shows that there is a division of tasks between physical and digital archive managers, although it does not yet have a clear organizational structure and task description. At the implementation stage, the archival system has run in a hybrid manner and is integrated in administrative activities, but it has not been optimal in terms of archive shrinkage. Meanwhile, the supervision stage is actively carried out by the leadership through document checks and periodic evaluations, but it has not been systematically documented. Thus, it is necessary to strengthen a more structured, formal, and sustainable archival system to increase the effectiveness of administrative order in the pesantren environment.